Variation in crop zinc concentration influences estimates of dietary Zn inadequacy - Bevis, Leah E. M.; Hestrin, Rachel (Public Library of Science, 2020)
The use of FCTs to calculate Zn intake overestimated the risk of dietary inadequacy for children who primarily consumed staple crops that were produced on household farms, but underestimated the risk for children who primarily consumed staple crops that were purchased at market. More information on the Zn content of staple crops in developing countries could lead to more accurate estimates of dietary intake and associated deficiencies.